Commentary—Liberty’s Forgotten Refugees? Engendering Assembly - Susan Frelich Appleton (Washington University Law Review, 2012)
This paper addresses three specific issues: Professor Inazu‘s treatment of the always-contested divide between public and private, his overly narrow reading of the Supreme Court‘s intimate association doctrine, and his failure to distinguish exclusion from subordination. Although asking the woman question illuminates some of what is absent from Professor Inazu‘s analysis, the paper offers these comments with both collegial enthusiasm for his scholarship and commitment to ―engaging with the ideas that Liberty’s Refuge sets forth.
Keywords: & quot; Liberty& #x27; s Refuge: The Forgotten Freedom of Assembly& quot; John Inazu; Freedom of assembly; Right to exclude; Group rights